Associations between parental socioeconomic position and health-seeking behaviour for diarrhoea and acute respiratory infection among under-5 children in Myanmar: a cross-sectional study. Issue 3 (26th March 2020) - Lwin, Kaung Suu; Nomura, Shuhei; Yoneoka, Daisuke; Ueda, Peter; Abe, Sarah Krull; Shibuya, Kenji
Abstract : Objectives: To examine the associations of parental social and economic position with health-seeking behaviour for diarrhoea and acute respiratory infection (ARI) among under-5 children in Myanmar and explore potential underlying mechanisms. Design: A cross-sectional study. Setting: A secondary dataset from the nationwide 2015–2016 Myanmar Demographic and Health Survey (MDHS). Participants: All under-5 children in the sampled households with reported symptoms of diarrhoea and ARI during the 2-week period preceding the MDHS survey interview. Primary and secondary outcome measures: Four parental health-seeking behaviours: 'seeking treatment', 'formal health provider', 'public provider' and 'private provider' were considered. Social and economic positions were determined by confirmatory factor analysis. Multilevel logistic regressions were employed to examine the associations of social and economic positions with health-seeking behaviours for diarrhoea and ARI. Mediation analyses were conducted to explore potential underlying mechanisms in these associations. Results: Of the 4099 under-5 children from the sampled households in MDHS, 427 (10.4%) with diarrhoea and 131 (3.2%) with ARI were considered for the analyses. For diarrhoea, social position was positively associated with seeking treatment and private provider use (adjusted OR: 1.60 (95% CIs: 1.07 to 2.38) and 1.83 (1.00 to 3.34), respectively). Economic position was positively associated with private provider use for diarrhoea (1.57 (1.07 to 2.30)). Negative associations were observed between social and economic positions with public provider use for diarrhoea (0.55 (0.30 to 0.99) and 0.64 (0.43 to 0.94), respectively). Social position had more influence than economic position on parental health-seeking behaviour for children with diarrhoea. No evidence for a significant association of social and economic position with health-seeking for ARI was observed. Conclusions: Social and economic positions were possible determinants of health-seeking behaviour for diarrhoea among children; and social position had more influence than economic position. The results of this study may contribute to improve relevant interventions for diarrhoea and ARI among children in Myanmar.